Surviving in the urban jungle: the role of foam nests as thermal insulator in Pleurodema borellii (Anura: Leptodactylidae) - Boggio, Ana Gimena (2024)
Urbanisation stands as a primary driver of biodiversity loss globally, reshaping natural landscapes and imposing novel environmental conditions upon organisms. This ecological novelty poses challenges, and species capable of thriving in urban environments are considered tolerant. Among vertebrates, anurans are the most susceptible to land-use changes, mainly due to their life history and morphological traits. They exhibit a great diversity of reproductive strategies and modes, among which the foam nest plays several important roles, such as moderating or buffering adverse conditions. In this study, we assessed the foam nest of Pleurodema borellii, an urban tolerant species, as a potential thermal insulator in the city of San Salvador de Jujuy, Argentina. We carried out our surveys within San Salvador and surrounding areas, focusing on urban and peri-urban environments. We measured the height, length, and internal temperature of 48 foam nests, as well as the temperature of their immediate environment (water and air at one cm above the nest), over consecutive days from the first day until the nest disappeared. Finally, we collected four to five embryos from each foam nest once a day to identify their developmental stage. Our results suggest that foam nests not only mitigate low temperatures but also buffer against the heat of urban environments. These findings suggest that the foam nest could be one of the traits that facilitates the occurrence of this anuran species in the city and therefore may explain its tolerance to urbanisation.